Analisis determinan kelaparan - Ikeu Tanziha; Hidayat Syarif; Clara M Kusharto; Hardinsyah Hardinsyah; Dadang Sukandar (Media Gizi dan Keluarga, 2005)
The purpose of this study was to analyze the prevalence and determinants of hunger. The study design was a cross-sectional study. The research was conducted in four areas (Bogor Municipality, Garut, Karawang, and Pandeglang Districts) during July-October 2003. A systematic stratified random sampling was applied to select 400 households consisted of 1351 individuals. The data collected include socio economic and demographic data, perception on hunger, and food expenditure. Logistic regression was applied to analyze determinants of hunger. The results showed that qualitatively, prevalence of hunger was 9.8%, and main determinant of hunger was expenditure per capita.